2011
DOI: 10.1017/s0025315411001421
|View full text |Cite
|
Sign up to set email alerts
|

Methane seep molluscs from the Sinú–San Jacinto fold belt in the Caribbean Sea of Colombia

Abstract: Several species of bivalves belonging to families which are typically associated with reducing conditions, like those observed at methane seep sites, have been obtained in recent explorations of the Caribbean Sea margin off the coast of Colombia. The material has been collected at depths of around 500 m west of the Magdalena and Sinú deltas, located in the Sinú–San Jacinto fold belt. These bivalves correspond to the families Vesicomyidae (Calyptogena ponderosa, Vesicomya caribbea and Ectenagena modioliforma), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 32 publications
1
15
0
2
Order By: Relevance
“…Consequently, INVEMAR carried out six "Macrofauna" cruises (1998)(1999)(2000)(2001)(2002) on board of the B/I "Ancón" to fill the information gap concerning the Colombian soft bottom fauna between 10 and 520 m depth (Saavedra- Díaz et al 2000;Lattig and Reyes 2001;Borrero-Pérez et al 2002a, b;Cruz et al 2002;Gracia et al 2002Gracia et al , 2004Reyes and Santodomingo 2002;Roa-Varón et al 2003;Borrero-Pérez and Benavides-Serrato 2004;Campos et al 2004;Flórez-Romero et al 2007). The discovery of azooxanthellate coral communities ) and methane seep ecosystems (Gracia et al 2012) were among the most interesting results of these expeditions.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, INVEMAR carried out six "Macrofauna" cruises (1998)(1999)(2000)(2001)(2002) on board of the B/I "Ancón" to fill the information gap concerning the Colombian soft bottom fauna between 10 and 520 m depth (Saavedra- Díaz et al 2000;Lattig and Reyes 2001;Borrero-Pérez et al 2002a, b;Cruz et al 2002;Gracia et al 2002Gracia et al , 2004Reyes and Santodomingo 2002;Roa-Varón et al 2003;Borrero-Pérez and Benavides-Serrato 2004;Campos et al 2004;Flórez-Romero et al 2007). The discovery of azooxanthellate coral communities ) and methane seep ecosystems (Gracia et al 2012) were among the most interesting results of these expeditions.…”
Section: Introductionmentioning
confidence: 99%
“…The former belongs to a typical deep-sea genus of the Neogene wood-falls (Bertolaso and Palazzi, 1994). The latter belongs to Colloniidae Cossmann, 1917, a typical family from late Mesozoicrecent chemosynthesis-based communities (e.g., Kiel, 2008;Gill et al, 2005;Kaim et al, 2009;Sasaki et al, 2010;Gracia et al, 2012), and is the same species as found in other Miocene wood-falls from northern Italy (Bertolaso, personal observation). Two other remarkable occurrences, both represented by a significant number of specimens, contribute to detailing a palaeoenvironmental framework.The first, Leptochiton, is a typical woodfall genus in deep waters.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…In addition to the associated fauna, the geological characteristics of the area, such as accretionary prisms that favor cold seep formation, suggest the presence of such ecosystems in the region (Gracia et al, 2011) and the tolerance of E. aceroi to this habitat. Previous to this record, one member of the genus, E. strickrotti, was recorded from a hydrothermal vent site on the East Pacific Rise (Møller and Jones, 2007).…”
Section: Discussionmentioning
confidence: 99%